Analysis of Factors Affecting Interest and Behavior in the Use of Animal Health Information Systems in Central Java Province - Ebti Uji Rahayu; Endah Setyowati; Romy Hermawan (PT Publikasiku Academic Solution, 2023)
The National Animal Health Information System (iSIKHNAS) is an innovation from the Ministry of Agriculture that is used as a tool for collecting information in the field of animal husbandry and animal health. iSIKHNAS aims to provide services and benefits for all users, create efficiency and effectiveness in data and information management, iSIKHNAS can run well if accepted and utilized by officers in the field. This research was conducted to see what factors influence the interest and behavior of using iSIKHNAS by using the UTAUT acceptance method. The method used in this study is quantitative with analysis using SEM-PLS. The results of this study show that the three variables in UTAUT that influence interest in using iSIKHNAS are performance expectations, effort expectations, and social conditions, while usage behavior and utilization of information systems are influenced by facility conditions and usage interest. The hypotheses offered by UTAUT are empirically proven in this study.